A Robust and Efficient ECC-based Mutual Authentication and Session Key Generation Scheme for Healthcare Applications. - Ostad-Sharif, Arezou; Abbasinezhad-Mood, Dariush; Nikooghadam, Morteza (Journal of Medical Systems, 2019)
Telecare medicine information system (TMIS) has provided an efficient and convenient way for communications of patients at home and medical staffs at clinical centers. To make these communications secure, user authentication by medical servers is considered as a crucial requirement. For this purpose, many user authentication and key agreement protocols have been put forwrad in order to fulfil this vital necessity. Recently, Arshad and Rasoolzadegan have revealed that not only the authentication and key agreement protocols suggested by Amin and Biswas and Giri et al. are defenseless against the replay attack and do not support the perfect forward secrecy, but also Amin and Biswas's protocol is susceptible to the offline password guessing attack. Nonetheless, in this paper, we demonstrate that Arshad and Rasoolzadegan's and the other existing schemes still fail to resist a well-known attack. Therefore, to cover this security gap, a new user authentication and session key agreement protocol is recommended that can be employed effectively for offering secure communication channels in TMIS. Our comparative security and performance analyses reveal that the proposed scheme can both solve the existing security drawback and, same as Arshad and Rasoolzadegan's scheme, has low communication and computational overheads.